POTENSI PENGEMBANGAN INDUSTRI BATIK DI BANDAR LAMPUNG - Nur Efendi (Business Preneur: Jurnal Ilmu Administrasi Bisnis, 2022)
Batik is a product that is very popular with people. This industry is developing not only on the island of Java, but also across Indonesia, including Bandar Lampung. There are several batik enterprises that are developing in Bandar Lampung at small and medium scale. This research aims to identify the development potential of the batik industry in Bandar Lampung. The method of investigation used is descriptive and qualitative. Respondents to the research were Siger Roemah Batik and Rahmad Batik Lampung. Data collection techniques involving interviews with owners, employees and consumers, and compliance techniques. Data analysis based on SWOT analysis. The results showed that the batik industry in Bandar Lampung can be expanded. The external potential of the batik industry is fairly significant because it is supported by local government regulations concerning the use of batik clothing in government institutions and schools. The internal potential of the batik industry is in the medium category because there are still several internal problems that must be resolved, including the source of raw materials that must be sent from Java. The batik enterprises that has the first priority to be developed is Rahmad Batik Lampung's because it has great external potential and its internal potential is in the medium category. Meanwhile, Siger Roemah Batik's has external and internal potential which is in the medium category. Keywords: Batik, Development Potential, Internal and external potential.